Evidence-based security - Frenz, Christopher; Reiber, Jonathan (O'Reilly Media, Inc., 2023)
The business world faces an interesting paradox: although companies spend more money than ever on security solutions and protective technologies, breaches and other attacks continue to escalate. This raises the question: are we, as an industry, doing something wrong? With the increase in targeted cyberattacks, rising risk levels, and high-impact consequences, it's more important than ever to be able to answer that question. In this report, Christopher Frenz and Jonathan Reiber show CISOs, security directors, and security managers how to transform security from an artform to a science, with evidence-based solutions leading the way. You'll learn how to operationalize the MITRE ATTU&CK framework and enable your team to produce actionable results and meaningful metrics, and measurably improve your security posture.